Development of chitosan/pluronic F108/polyethersulfone (PES) nanofiltration (NF) membrane for oily wastewater treatment - Hamzah N.; Rohani R.; Hassan A.R.; Sharifuddin S.S.; Mohd Hafez Mohd Isa (American Institute of Physics Inc., 2024)
Indexed by WOS/ Scopus